Research progress on biodegradable polymer-based drug delivery systems for the treatment of knee osteoarthritis - Zhang, Jinchi; Zhang, Jinchao; Li, Hailong; Zhang, Huimin; Meng, Hongyan (Frontiers in Bioengineering and Biotechnology, 2025)
Knee osteoarthritis (KOA) is a disease that involves multiple anatomical and physiological changes in the knee tissues, including cartilage degeneration, bone remodelling and formation of bony encumbrances, which leads to clinical manifestations including pain, stiffness, swelling and limitation of knee function. Knee osteoarthritis is a chronic joint disease characterised by degenerative cartilage lesions and secondary osteophytes in the knee joint. The symptoms of knee osteoarthritis tend to progress slowly, and at this stage, the number of patients with KOA is increasing. However, due to the adverse effects and poor therapeutic outcomes following surgical treatment, intervention therapy through the utilisation of biodegradable polymeric materials is required. Currently, clinical aspects are mainly used to treat cartilage degeneration in patients with osteoarthritis of the knee by using different kinds of biodegradable biopolymer materials with excellent physical properties, histocompatibility and other properties, combined with a drug delivery system, which can reduce the level of inflammation and stiffness in the focal area, and maximise the restoration of the patient’s knee joint joint mobility and athletic ability. Based on the properties of the polymeric material drug delivery system, the polymeric material has a variable drug loading capacity that encapsulates hydrophobic/hydrophilic drugs and controls the release kinetics by regulating the composition and charge. This paper reviews the research progress of Poly (ε-caprolactone) (PCL), Poly(lactic acid) (PLA), Poly (lactic glycolic acid) (PLGA), Poly(ethylene glycol) (PEG) synthetic polymers and collagen, chondroitin sulfate, other natural polymers based drug delivery systems for the treatment of knee osteoarthritis, and explains that different biodegradable polymeric materials have been widely used for the treatment of knee osteoarthritis. However, there are still issues of degradability, toxicity, compatibility, and durability and safety of the drug delivery system of degradable materials that need to be addressed in further clinical trials. As biodegradable biomedical materials continue to be explored, eventually idealized polymeric materials will stand out in the treatment of KOA.